Komunikasi Efektif dan Monitoring, Model Evaluasi Pendidikan Berkarakter Melalui Pembiasaan Ibadah Sehari-hari di Masa Pandemi - Sitti Chadidjah; Iwan Hermawan (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2021)
To break the deadlock in the character education process in schools during the COVID-19 pandemic, several schools are trying to implement a learning model that leads to this goal. One of the models applied at SMP Negeri 44 Bandung is an effective communication evaluation model through the habit of students' daily worship with collages. in the form of photos of activities that are being carried out and effective communication between teachers and students, students and students. The homeroom teacher and picket students monitor the implementation of this habituation activity. Every day students collect collages of activities for students on duty or picket through whats up media. After tidying up the collage, the students are handed over to the homeroom teacher and PAI teacher to be assessed. PAI teachers will assess two core competencies, namely social attitudes, and spiritual attitudes. Through a descriptive qualitative approach, researchers try to uncover these phenomena through triangulation techniques. The results achieved by using this model can grow students' daily worship habits and reduce less useful activities. Moreover, students felt cared for by the PAI teacher and his friends who were on picket at the time so that even though students were learning online, they felt the presence of a teacher and friend in their activities. In addition, it can be a break for students in carrying out every action taken. Untuk memecah kebuntuan proses pendidikan karakter di sekolah pada masa pandemi covid 19, beberapa sekolah berupaya menerapkan model pembelajaran yang mengarah pada maksud tersebut.Salah satu model yang diterapkan di SMP Negeri 44 Bandung adalah model evaluasi komunikasi efektif melalui pembiasaan ibadah sehari-hari siswa dengan kolase berupa foto-foto aktivitas yang sedang dijalankan dan komunikasi efektif antara guru dan siswa, siswa dan siswa. Walikelas dan siswa piket memonitor terlaksananya aktivitas pembiasaan ini Setiap hari siswa mengumpulkan kolase kegiatan kepada siswa yang bertugas atau piket melalui media whats up. Setelah rapih kolase siswa diserahkan kepada wali kelas dan guru PAI untuk dinilai. Guru PAI akan menilai dua kompetensi inti yaitu sikap social dan sikap spiritual. Melalui pendekatan kualitatif deskriptif peneliti berusaha mengungkap fenomena tersebut melalui teknik triangulasi. Hasil yang dicapai dengan menggunakan model ini, mampu menumbuhkan kebiasaan ibadah harian siswa serta mengurangi aktifitas yang kurang bermanfaat. Terlebih siswa merasa diperhatikan oleh guru PAI dan temannya yang sedang piket saat itu sehingga siswa meski pembelajaran daring, merasakan hadirnya seorang guru dan teman dalam aktivitasnya. Selain itu dapat menjadi rem bagi siswa dalam melakukan setiap tindakan yang dilakukan.